Thiadiazole Carbamates: Potent Inhibitors of Lysosomal Acid Lipase and Potential Niemann-Pick Type C Disease Therapeutics - Rosenbaum, Anton I. (2010)
Niemann-Pick type C (NPC) disease is a lysosomal storage disorder characterized at the cellular level by abnormal accumulation of cholesterol and other lipids in lysosomal storage organelles. Lysosomal acid lipase (LAL) has been recently identified as a potential therapeutic target for NPC. LAL can be specifically inhibited by a variety of 3,4-disubstituted thiadiazole carbamates. An efficient synthesis of the C(3) oxygenated/C(4) aminated analogues has been developed that furnishes the products in high yields and high degrees of purity. Common intermediates can also be used for the synthesis of the C(3) carbon substituted derivatives. Herein we tested various thiadiazole carbamates, amides, esters, and ketones for inhibition of LAL. In addition, we tested a diverse selection of commercially available non-thiadiazole carbamates. Our studies show that, among the compounds examined herein, only thiadiazole carbamates are effective inhibitors of LAL. We present a mechanism for LAL inhibition by these compounds whereby LAL transiently carbamoylates the enzyme similarly to previously described inhibition of acetylcholinesterase by rivastigmine and other carbamates as well as acylation of various lipases by orlistat.